Cross-border reproductive healthcare attitudes and behaviours among women living in Florence, Italy - Stephanie Meier; Jaziel Ramos-Ortiz; Kelsie Basille; Alyson C. D'Eramo; Adria M. Diaconu; Lesley J. Flores; Savannah Hottle; Kaylee Mason-Yeary; Yumary Ruiz; Andrea L. DeMaria (BMC, 2022)
Abstract Background The number of women living in Italy and seeking cross-border reproductive care (CBRC), especially for medically assisted reproduction (MAR), has increased. The purpose of this study was to explore CBRC attitudes and behaviours among a cohort of reproductive-aged women who have never engaged in CBRC to gauge social and cultural perceptions and gain a deeper understanding of family planning discourse. Methods In-depth interviews were conducted during May - June 2018 with 30 women aged 18-50 living in or around Florence, Italy and enrolled in the Italian healthcare system. Interviews offered in-depth insight into CBRC attitudes, behaviours, and experiences among a cohort of women living in Italy who had never engaged in CBRC. Researchers used an expanded grounded theory through open and axial coding. Emergent themes were identified via a constant comparison approach. Results Three themes and two subthemes emerged from the data. Participants discussed how limitations in Italy's access to MAR can lead women to seek reproductive healthcare in other countries. Women had mixed feelings about the effect of religion on legislation and reproductive healthcare access, with many views tied to religious and spiritual norms impacting MAR treatment-seeking in-country and across borders. Participants perceived infertility and CBRC-seeking as socially isolating, as the motherhood identity was highly revered. The financial cost of traveling for CBRC limited access and exacerbated emotional impacts. Conclusions Findings offered insight into CBRC perceptions and intentions, presenting a deeper understanding of the existing family planning discourse among reproductive-aged women. This may allow policymakers and practitioners to address social and cultural perceptions, increase access to safe and effective local care, and empower women in their family planning decisions.